2013
DOI: 10.1590/s0001-37652013005000020
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of sympathetic chain in Saguinus niger

Abstract: Saguinus niger popularly known as Sauim, is a Brazilian North primate. Sympathetic chain investigation would support traumatic and/or cancer diagnosis which are little described in wild animals. The aim of this study was to describe the morphology and distribution of sympathetic chain in order to supply knowledge for neurocomparative research. Three female young animals that came death by natural causes were investigated. Animals were fixed in formaldehyde 10% and dissected along the sympathetic chain in neck,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Two predominant patterns were seen in pacas: celiac and cranial mesenteric ganglion and the celiacomesenteric ganglion, as observed in cats and in rabbits (Ribeiro et al, 2000b;Sasahara et al). The paca celiac ganglion presented elongated shape as observed in Sauim (Saguinus niger), a neotropical primate (Pinto et al, 2013).In humans, several shapes were observed as laminar, nodular and sickle. In cats the shape also varies between rectangular, elliptic, irregular and piriformis and in rats the format is pear shape (Hamer & Santer, 1981;Ribeiro et al, 2000b).…”
Section: Discussionmentioning
confidence: 88%
“…Two predominant patterns were seen in pacas: celiac and cranial mesenteric ganglion and the celiacomesenteric ganglion, as observed in cats and in rabbits (Ribeiro et al, 2000b;Sasahara et al). The paca celiac ganglion presented elongated shape as observed in Sauim (Saguinus niger), a neotropical primate (Pinto et al, 2013).In humans, several shapes were observed as laminar, nodular and sickle. In cats the shape also varies between rectangular, elliptic, irregular and piriformis and in rats the format is pear shape (Hamer & Santer, 1981;Ribeiro et al, 2000b).…”
Section: Discussionmentioning
confidence: 88%
“…at the cervical vertebrae level or between the seventh and eighth cervical vertebrae. Pinto et al (17) conducted a study on tamarins, which are classified as primates, and found the cervicothoracic ganglion under the second rib. The shape of the ganglion depends on the species.…”
Section: Fig 1 Left Cervicothoracic Ganglion In Adult Cat Cervicothoracic Ganglion On the Left Side In Adult Domestic Catmentioning
confidence: 99%